2008
DOI: 10.1177/1934578x0800300238
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of Selected Japanese and New Zealand Liverworts

Abstract: Liverworts are rich sources of biologically active substances. Recent topics relating to the chemical constituents found in several Japanese and New Zealand liverworts and their biological activity and chemosystematics are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…41 The bazzanane sesquiterpenoids have been also found in F. squarrosula. 14,52 Chemical analysis of the New Zealand Frullania falciloba from different collections showed the presence of β-bazzanene ( 27), but no other bazzananes were detected. This species produces 3-methoxy-3′,4′-methylenedioxybibenzyl (35), as the main component, along with the fusicoccane diterpenoid, fusicogigantepoxide.…”
Section: Chemosystematic Approachmentioning
confidence: 99%
“…41 The bazzanane sesquiterpenoids have been also found in F. squarrosula. 14,52 Chemical analysis of the New Zealand Frullania falciloba from different collections showed the presence of β-bazzanene ( 27), but no other bazzananes were detected. This species produces 3-methoxy-3′,4′-methylenedioxybibenzyl (35), as the main component, along with the fusicoccane diterpenoid, fusicogigantepoxide.…”
Section: Chemosystematic Approachmentioning
confidence: 99%
“…[ 9 , 10 , 11 ]. Others, Trichocolea mollissima, T. tomentella and T. lanata , possess prenyl-phenyl ethers that are mildly fungicidal [ 12 , 13 ]. Recently, a structural study aimed at understanding the structure of early land plants through the comparison of the tube and cell-sheet from Cambrian-to-Devonian microfossils with experimentally degraded modern liverworts, suggested that the presence of phenolic compounds was responsible for the protection of lower epidermal tissues from the soil microbe attack, and provided dimensional stability to the remains of early marchantioid liverworts similar in some ways to modern Marchantia and Conocephalum [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many liverworts are endemic to the southern hemisphere, including Oceania and South America. Recently, we have reported the structures of new sesqui- and diterpenoids from New Zealand liverworts [ 3 ]. We also reported the isolation of new sesquiterpenoids 1 and 2 from an unidentified Gackstroemia species from New Zealand [ 4 ].…”
Section: Introductionmentioning
confidence: 99%